Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences ... - Finstad, Anders Gravbrøt; Berg, Ole Kristian; Ulvan, Eva; Helland, Ingeborg; Ugedal, Ola (Norwegian University of Science and Technology, 2019)
Brown trout (Salmo trutta) and Arctic char (Salvelinus alpinus) were sampled in 20 lakes located along an altitudinal gradient (36 - 850 m.a.s.l.) in central Scandinavia. 10 of these lakes where trout only populations (allopatric) and in 10 trout and char co-existed. In addition, Three spined stickleback (Gasterosteus aculeatus L.) and European eel (Anguilla Anguilla L) co-occurs in most lakes below the marine transgression line. However, these species where not collected using the present gill-net series. Also, two of the lakes (Slipstikken and Grisbakktjørna) had a scares population of burbot (Lota lota L.) (catch of burbot not recorded). The sympatric lakes, with the exception of Kjerråtjønnin were sampled three times (spring 2008 – autumn 2008 – spring 2009), and the allopatric lakes were sampled two times (autumn 2008 – spring 2009). Autumn samples were collected just before ice formation and spring samples in 2008 somewhat after and 2009 just after ice breakup. At each sampling period fish were sampled ...